2022
DOI: 10.3390/cancers14246028
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Warburg Effect with Focus on Lactate

Abstract: Rewired metabolism is acknowledged as one of the drivers of tumor growth. As a result, aerobic glycolysis, or the Warburg effect, is a feature of many cancers. Increased glucose uptake and glycolysis provide intermediates for anabolic reactions necessary for cancer cell proliferation while contributing sufficient energy. However, the accompanying increased lactate production, seemingly wasting glucose carbon, was originally explained only by the need to regenerate NAD+ for successive rounds of glycolysis by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 142 publications
(186 reference statements)
0
30
0
Order By: Relevance
“…Confirmation of FTC is challenging even after thyroid lobectomy, as areas where there is capsular or vascular invasion may be missed. Another of the challenges that is persistent is the inability to accurately diagnose the extent of vascular invasion, which is required for the differentiation of mi-FTC from wi-FTC [ 86 , 211 ]. That a low-risk WDTC has become high-risk or de-differentiated may also go unnoticed following FNAC, diagnostic lobectomy, or total thyroidectomy [ 10 , 54 , 55 , 57 , 86 , 98 , 162 ].…”
Section: Multi-omics Of Follicular Carcinoma and Other Thyroid Tumorsmentioning
confidence: 99%
“…Confirmation of FTC is challenging even after thyroid lobectomy, as areas where there is capsular or vascular invasion may be missed. Another of the challenges that is persistent is the inability to accurately diagnose the extent of vascular invasion, which is required for the differentiation of mi-FTC from wi-FTC [ 86 , 211 ]. That a low-risk WDTC has become high-risk or de-differentiated may also go unnoticed following FNAC, diagnostic lobectomy, or total thyroidectomy [ 10 , 54 , 55 , 57 , 86 , 98 , 162 ].…”
Section: Multi-omics Of Follicular Carcinoma and Other Thyroid Tumorsmentioning
confidence: 99%
“…Tumor suppressor p53 and oncogenes (SRC, AKT, RAS) are linked to the transcription factors HIF and oncogenic MYC. All the glycolytic enzymes have isoenzymes which are targets for HIF with hypoxia-response elements (HRE) in their promoter region [23]. Adv Bioeng Biomed Sci Res, 2023 Glucose Transporters and Metabolic Enzymes Link in The Warburg Effec 1.…”
Section: Krasmentioning
confidence: 99%
“…Adv Bioeng Biomed Sci Res, 2023 Glucose Transporters and Metabolic Enzymes Link in The Warburg Effec 1. Glucose Transporters (GLUT 1-4): Glucose transporters 1 and 3 were the earliest to be discovered as HIF targets due to their enhancement of Glucose transport which facilitated the Warburg effect (23). Studies have demonstrated very strong associations between GLUT 1 expression and the Warburg effect.…”
Section: Krasmentioning
confidence: 99%
“…41,48,49,50 There are different factors that can lead to a switch to the Warburg effect, 42 such as mitochondrial defects and increased expression or amplification of relevant genes 51 that, when overexpressed, contribute to increased glycolysis observed in cancer cells, including testicular cancer, promoting tumour growth and aggressiveness. 41,52 In cancer, some of the genes that are overexpressed in glycolysis include hexokinase-1, hexokinase-2, glucose phosphate isomerase, aldolase A and glyceraldehyde-3-phosphate dehydrogenase. Hexokinase-1 and -2 are enzymes that catalyse conversion of glucose to glucose-6-phosphate, a first step in glycolysis.…”
Section: Mitochondria In Testicular Cancermentioning
confidence: 99%